Staphylococcal enterotoxin B (SEB) toxin of Staphylococcus aureus and the detection methods - Thu, Nguyễn Thị Hoài; Minh, Nghiêm Ngọc (Vietnam Journal of Biotechnology, 2018)
Staphylococcal enterotoxins (SEs) secreted by Staphylococcus aureus is one of the principal causes of food poisoning. The SEs are superantigens; they are highly stable, resisting most proteolytic enzymes and thus keeping activity in the gastrointestinal tract after being ingestion. In particular, heat-stable enterotoxin is one of the most important property related to food safety. They are not degraded at 100°C for 30 minutes, even at 121oC for 28 minutes, the SEs retain biological activity. Heat resistance of SEs in foods is higher than in the culture medium. Staphylococcus aureus (S. aureus) produces more than 20 different types of enterotoxins, including SEA to SEE, SEG to SER and SEU. Among these, Staphylococcal enterotoxin B (SEB) is a powerful toxin, heat-stable, water-soluble and is a common cause of food poisoning. Moreover, SEB is one of the harmful or hazardous agents used as biological weapons in bioterrorism or biological warfare. Therefore, determining presence of SEB toxin in food is extremely important. In this review, we introduce the most basic features about S. aureus; about SEB toxin and conventional methods for SEB diagnosis, detection. Especially, we focus on rapid detection strip based on an immunochromatography; this technique is an highly sensitive, rapid, easy for use and storage.